A first step towards a consensus static in vitro model for simulating full-term infant digestion. (1st February 2018) - Ménard, O.; Bourlieu, C.; De Oliveira, S.C.; Dellarosa, N.; Laghi, L.; Carrière, F.; Capozzi, F.; Dupont, D.; Deglaire, A.
Highlights: Static in vitro model for simulating full-term infant digestion. Comparison of the infant model with the adult international consensus protocol. Structural characterization during digestion. Biochemical characterization of the lipolysis and proteolysis products. Abstract: In vitro alternatives to clinical trials are used for studying human food digestion. For simulating infant digestion, only a few models, lacking physiological relevance, are available. Thanks to an extensive literature review of the in vivo infant digestive conditions, a gastrointestinal static in vitro model was developed for infants born at term and aged 28 days. The model was applied to the digestion of a commercial infant formula. Kinetics of digestion, as well as the structural evolution, were compared with those obtained while submitting the same formula to the adult international consensus protocol of in vitro static digestion. The kinetics of proteolysis and lipolysis differed according to the physiological stage resulting mainly from the reduced level of enzymes and bile salts, as well as the higher gastric pH in the infant model. This in vitro static model of infant digestion is of interest for scientists, food or pharmaceutical manufacturers.